Pemanfaatan Digital Marketing Shopee dan Shopee Live sebagai Optimalisasi Pemasaran Fashion Muslimah “Gamaleea” dalam Menaikkan Omset Penjualan UMKM - Putri, Synthia Sumartini; Almini, Almini (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The use of digital marketing is currently being greatly utilized by micro, small and medium enterprises (MSMEs). What micro, small and medium businesses use is Shopee Live or Shopee. With Shopee, it helps people meet household needs. Like the micro, small and medium Muslim fashion business "Gamaleea" utilizing the shopee or shopee live marketplace. Data collection techniques use observation, interviews and documentation. The results of the data that researchers found were that the Muslim fashion business "Gamaleea" focused on marketing using the Shopee marketplace or Shopee Live. Shopee live is useful for increasing sales in the Muslim fashion sector.